Fuktkvotens inverkan på oljeupptag och pigmentinträngning i tall (Pinus sylvestris L.) och gran (Picea abies L. Karst) vid impregnering med Linotechmetoden - Sjöström, Anna (SLU/Dept. of Forest Ecology and Management, 2008)
Wood has always been an important material for people, and it is used for many applications. As for example, fuel for cooking and heating houses, construction materials and for constructing means of transport. Since wood also is a material that with time biologically degrades due to activity by micro organisms and wood fungi it is important to find ways to protect and further lengthen the life span of the material when in service. One method is to decrease the amount of water in the material by impregnation with an hydrophobic oil. The Linotech method which uses only pure linseed oil is one such possible method.